Improving The Capability Of Madrasah Teachers In Conducting Diagnostic Assessments And Differentiation Learning In Tiris District Probolinggo - Prasetiya, Benny; Halili, Heri Rifhan (Jurnal Penelitian IPTEKS, 2024)
Improving the quality of learning is crucial in the educational context. Teachers, as the main agents in the learning process, are responsible for creating an effective and enjoyable learning environment. This research focuses on the implementation of the Independent Curriculum in madrasas in Probolinggo Regency, particularly in the Tiris District. By involving 30 madrasas, this study aims to enhance teachers' abilities in conducting diagnostic assessments and differentiated learning. The Participatory Rural Appraisal (PRA) approach is used to actively involve teachers in designing and implementing more effective learning strategies. Through this approach, teachers are not merely recipients of instructions but active collaborators involved in every stage of planning and implementation. PRA enables teachers to deeply understand the needs and potential of students, allowing them to design more targeted and contextually appropriate learning strategies. Through two stages of training and mentoring, madrasa teachers are provided with an in-depth understanding of diagnostic assessments and differentiated learning. The evaluation involves both teachers and students as assessment subjects to measure the positive impact of implementing these learning strategies. The research results indicate a significant increase in teachers' knowledge and skills regarding the planning and execution of differentiated learning. Teachers have succeeded in creating an inclusive learning environment, motivating students, and improving learning outcomes. Diagnostic assessments also provide valuable guidance for teachers in designing learning strategies that meet the individual needs of students. It is hoped that this improvement in learning quality will positively impact students' learning experiences and serve as a model for other madrasas in enhancing the quality of education. The implementation of the Independent Curriculum through the PRA approach has proven effective in encouraging positive changes in learning practices in madrasas in Probolinggo Regency